West Meets East in a New Two-Polarities Model of Personality: Combining Self-Relatedness Structure With Independent-Interdependent Functions - Fan, Weiqiao; Li, Mengting; Leong, Frederick; Zhou, Mingjie (Frontiers in Psychology, 2021)
Self and relatedness are the two most essential dimensions of personality, as indicated in many personality theories, and have been supported by numerous empirical studies conducted in the western (individualistic) and eastern (collectivist) contexts. However, because of a confusion or failure to distinguish the structure and function of personality, popular theories (e.g., the Big Five model) do not make logic distinctions between these two basic personality dimensions. In terms of the cultural-relevant feature, both self and relatedness and their specific aspects may be variously highlighted in different cultural settings. On the basis of a re-examination of several crucial two-dimension (namely, self and relatedness) personality theories derived from the east and west, we reconstruct a new two-polarities personality model to include not only self and relatedness but also the independent and interdependent functions in terms of some popular personality theories from western and eastern cultures. Theoretically and empirically, self and relatedness should be the basic structures of personality, whereas independence and interdependence should be the basic functions of personality. Self and relatedness have independent and interdependent functions; however, due to the cultural relevance of personality, the functions should be variously emphasized in different contexts. Several possible future research directions are discussed.